Structural congenital anomalies in resource limited setting, 2023: A systematic review and meta-analysis. - Yohannes Fikadu Geda; Yirgalem Yosef Lamiso; Tamirat Melis Berhe; Seid Jemal Mohammed; Samuel Ejeta Chibsa; Tadesse Sahle Adeba; Kenzudin Assfa Mossa; Seblework Abeje; Molalegn Mesele Gesese (PLoS ONE, 2023)
Background A number of studies have looked at neonatal structural birth defects. However, there is no study with a comprehensive review of structural anomalies. Therefor we aimed to verify the best available articles to pool possible risk factors of structural congenital anomalies in resource limited settings. Setting Genuine search of the research articles was done via PubMed, Scopes, Cochrane library, the Web of Science; free Google database search engines, Google Scholar, and Science Direct databases. Published and unpublished articles were searched and screened for inclusion in the final analysis and Studies without sound methodologies, and review and meta-analysis were not included in this analysis. Participants This review analyzed data from 95,755 women who have birthed from as reported by primary studies. Ten articles were included in this systematic review and meta-analysis. Articles which have no full information important for the analysis and case reports were excluded from the study. Results The overall pooled effect estimate of structural congenital anomalies was 5.50 [4.88-6.12]. In this systematic review and meta-analysis maternal illness effect estimate (EI) with odds ratio (OR) = 4.93 (95%CI 1.02-8.85), unidentified drug use OR = 2.83 (95%CI 1.19-4.46), birth weight OR = 4.20 (95%CI 2.12-6.28), chewing chat OR = 3.73 (95%CI 1.20-6.30), chemical exposure OR = 4.27 (95%CI 1.19-8.44) and taking folic acid tablet during pregnancy OR = 6.01 (95%CI 2.87-14.89) were statistically significant in this meta-regression. Conclusions The overall pooled effect estimate of structural congenital anomalies in a resource limited setting was high compared to better resource countries. On the Meta-regression maternal illness, unidentified drug use, birth weight, chewing chat, chemical exposure and never using folic acid were found to be statistically significant variables Preconception care and adequate intake of folic acid before and during early pregnancy should be advised.